The digital readiness of agricultural advisory professionals: A South African case study - von Maltitz, Lindie; Van Niekerk, Johan A.; Davis, Kristin E. (2024)
Agricultural advisory services link producers, the government, the research community, and credit and input supply organisations. This vital role can be enhanced through the efficient use of digital platforms, especially in South Africa, where the advisor-to-producer ratio was last recorded to be 1:1019. According to the last census conducted in South Africa, 92.1% of households own a mobile phone, and only 21.1% do not have access to the internet, providing the platform for timeous interaction between advisors and their clients. The affordability of technology and data services, network coverage, and digital literacy are obstacles in the country that need to be addressed if access to ICTs is to be improved. This article focuses on the readiness of South African agricultural advisors to use digital platforms. Survey research was used to collect data from professionals, and the data was evaluated using a survey instrument that was developed based in part on similar work done in Rwanda. The results show that although most advisors are ready to use digital platforms, many obstacles must be addressed for efficient application.